Web strategy and social media in the craft microenterprises of Basilicata - Pencarelli, Tonino; Caravelli, Antonietta (Piccola Impresa / Small Business, 2017)
This paper analyzes the factors that influence the use of digital marketing tools and those that affect their effectiveness, the resulting benefits, and the barriers that limit their use. Following the analysis of the literature, we have formulated research hypotheses. They have been empirically tested on a sample of 42 craft microenterprise from Basilicata, to which was provided a questionnaire by telephone interview. The obtained results were analyzed together with the data provided by the AIDA database by contingency tables and the chi-square statistical test. The salientness of the sample analyzed limits the reliability of the statistical test to the most significant variables. However the study provides a contribution to the analysis of the causes of limited Internet access by micro-businesses in Basilicata, suggesting managerial and public policy guidance to increase competitiveness of handicraft industry.